Software process improvement and capability determination : 18th International Conference, SPICE 2018, Thessaloniki, Greece, October 9-10, 2018, Proceedings /: 18th International Conference, SPICE 2018, Thessaloniki, Greece, October 9-10, 2018, Proceedings. (2018) - Unknown
No abstract available